Clear Cell Carcinoma Compared to Serous Carcinoma in Early Ovarian Cancer: Same Prognosis in a Large Randomized Trial. Issue 1 (1st January 2009) - Timmers, P. J.; Zwinderman, A. H.; Teodorovic, I.; Vergote, I.; Trimbos, J. B.
Abstract : Background: An analysis was performed comparing survival of patients with clear cell carcinoma (CCC) to patients with serous adenocarcinoma (SAC) in early ovarian cancer. Furthermore, a literature search was done to clarify the clinical and histopathological features of clear cell tumors of the ovary. Methods: Between November 1990 and March 2000, 448 patients with ovarian cancer International Federation of Gynecology and Obstetrics stages I to IIa were enrolled in the European Organisation for Research and Treatment of Cancer-Adjuvant Chemotherapy in Ovarian Neoplasm Trial, a randomized study comparing adjuvant platinum-based chemotherapy to observation after surgical treatment in patients with early ovarian cancer. Results: Sixty-three patients (14.1%) with CCC were compared with 156 patients (34.8%) with serous tumors. A significant difference was found in the International Federation of Gynecology and Obstetrics stage Ic with capsule rupture, 28 (44.4%) of 63 patients with CCC and 29 (18.6%) of 156 patients with SAC ( P < 0.001). Recurrences occurred in 25% of the patients, and this was similar in the CCC and SAC groups. No significant difference was found in overall survival between patients with CCC and patients with SAC in both treatment arms together. In the observation arm, the 5-year disease-free survival was 71% in the CCC group versus 61% in the SAC group, whereas in the chemotherapy arm, the 5-year disease-free survival was higher in the SAC group compared with the CCC group (78% vs 60%). Both differences were not statistically significant. Conclusions: The present study showed no worse prognosis in patients with CCC as compared with patients with serous carcinoma in early ovarian cancer.